Prospective Monitoring of Donor-specific Anti-HLA Antibodies After Intestine/Multivisceral Transplantation: Significance of De Novo Antibodies. Issue 8 (August 2015) - Kubal, Chandrashekhar; Mangus, Richard; Saxena, Romil; Lobashevsky, Andrew; Higgins, Nancy; Fridell, Jonathan; Tector, A. Joseph
Abstract : Background: Presence of circulating donor-specific antibodies (DSA) may be associated with worse clinical outcomes after intestine/multivisceral transplantation. Methods: In 79 intestine/multivisceral recipients, sera were prospectively screened for DSA by Luminex Single antigen test at 1, 3, 6, 9, 12, 18, 24, and 36 months after transplantation. Standard immunosuppression included thymoglobulin-rituximab induction and tacrolimus-prednisone maintenance. C4d staining was performed retrospectively on biopsies in patients that developed acute rejection (AR). Results: Twenty-two (28%) patients developed de novo DSA at a median posttransplant period of 3 (1-36) months. De novo DSA were observed in 10 of 40 liver-including and 12 of 39 liver-excluding transplants ( P = 0.57). Occurrence of AR was slightly higher in patients with de novo DSA (45% vs 33%, respectively; P = 0.41). Similarly, chronic rejection (14% vs 5%; P = 0.21) and graft loss due to AR (18% vs 7%; P = 0.14) were numerically higher in patients with de novo DSA. Only 35% patients experiencing AR had circulating de novo DSA at the time of AR. Antibody-mediated rejection was diagnosed in 6 patients based on C4d staining, of these 2 patients had circulating de novo DSA at the time of biopsy. Conclusions: De novo DSA formation, particularly early in the posttransplant course may be associated with trends toward worse outcomes. However, its significance in the pathophysiology of AR remains uncertain. Studies focusing mechanisms of DSA-related graft injury and intragraft DSA detection might provide further insight into this issue. Abstract : The development of donor specific antibodies after intestinal and multivisceral transplantation is associated with a modest increase in acute and chronic rejection and graft loss.